Impacts of cover crop planting dates on soils after four years. (30th March 2020) - Ruis, Sabrina J.; Blanco‐Canqui, Humberto; Elmore, Roger W.; Proctor, Christopher; Koehler‐Cole, Katja; Ferguson, Richard B.; Francis, Charles A.; Shapiro, Charles A.
Abstract: Impacts of cover crop (CC) mixes and early CC planting on soil properties, CC biomass production, and CC biomass C input are not well understood. We assessed CC planting date (pre‐ or post‐harvest) and CC type (rye [ Secale cereale L.], mix of winter pea [ Pisum sativum L.], hairy vetch [ Vicia villosa L.], rye, and radish [ Raphanus sativus L.], or no CC) effects on soil physical properties, organic matter, and CC biomass C input under three no‐till continuous corn ( Zea mays L.) and corn‐soybean ( Glycine max L.) sites in the eastern Great Plains after 4 yr. Across sites and years, pre‐harvest‐planted CCs produced 0.81 ± 0.52 (mean ± SD), post‐harvest‐planted 0.59 ± 0.44, rye 0.83 ± 0.52, and mix 0.57 ± 0.42 Mg biomass ha −1 . Compared to no CC, pre‐ and post‐harvest–planted CC effects varied by site. Pre‐harvest–planted CCs increased wet‐aggregate stability by 17% and particulate organic matter by 31% under continuous corn at one of three sites compared with post‐harvest‐planted CCs. Similarly, the CC mix had variable effects on cone index but reduced bulk density by 7% at one site under continuous corn and increased wet‐aggregate stability by 21% at another site under corn−soybean. Planting date, but not CC type, effects were slightly more evident under continuous corn than corn−soybean. Across sites and years, pre‐harvest‐plant CC had 0.29 ± 0.38 Mg biomass C ha −1, post‐harvest‐planted 0.22 ± 0.30, rye 0.33 ± 0.37, and the mix 0.16 ± 0.27. Low CC biomass (<1 Mg ha −1 ) production may explain the limited CC effects. Overall, pre‐harvest‐planted CCs and CC mixes had minimal effects on soil properties in this region after 4 yr.